2013
DOI: 10.1007/s00249-013-0928-7
|View full text |Cite
|
Sign up to set email alerts
|

Use of a combination of the RDC method and NOESY NMR spectroscopy to determine the structure of Alzheimer’s amyloid Aβ10–35 peptide in solution and in SDS micelles

Abstract: The spatial structure of Alzheimer's amyloid Aβ10-35-NH2 peptide in aqueous solution at pH 7.3 and in SDS micelles was investigated by use of a combination of the residual dipolar coupling method and two-dimensional NMR spectroscopy (TOCSY, NOESY). At pH 7.3 Aβ10-35-NH2 adopts a compact random-coil conformation whereas in SDS micellar solutions two helical regions (residues 13-23 and 30-35) of Aβ10-35-NH2 were observed. By use of experimental data, the structure of "peptide-micelle" complex was determined; it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…One NMR study found Aβ 1–40 to adopt an 3 10 -helix in residues 13–23 in aqueous environment (PDB ID 2LFM) [19]. Another NMR study found Aβ 10–35 to adopt an α-helix in residues 13–23 and 30–35 inside SDS micelles [20]. However, at pH 7.3 Aβ 10–35 is unstructured and adopts a compact random-coil conformation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One NMR study found Aβ 1–40 to adopt an 3 10 -helix in residues 13–23 in aqueous environment (PDB ID 2LFM) [19]. Another NMR study found Aβ 10–35 to adopt an α-helix in residues 13–23 and 30–35 inside SDS micelles [20]. However, at pH 7.3 Aβ 10–35 is unstructured and adopts a compact random-coil conformation.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, one attempt to determine the NMR structure without TFE at physiological conditions, revealed Aβ to adopt a 3 10 -helical structure incongruent with previous α-helical observations [19]. Finally, another NMR study used micelles to determine the structure of Aβ 10–35 and found it to possess two α-helical regions within residues 13–23 and 30–35 [20]. …”
Section: Introductionmentioning
confidence: 99%
“…Several Aβ fragments react similarly to the parent peptides when placed in the SDS micelle system. In particular, different studies have been performed to investigate the behavior in SDS micelles of Aβ fragments encompassing residues 10 Y-M 35 [ 38 , 39 , 40 , 41 ]. Among these fragments, Aβ(25−35) represents the shortest sequence of Aβ able to mimic the biological behavior of the full-length amyloid peptides, forming large β-sheet aggregates and reproducing the toxicity of the peptide [ 21 , 42 , 43 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, interactions of different drugs with phospholipid aggregates can be effectively studied by NMR using model membranes. One of the commonly used membrane models in NMR work is the sodium dodecyl sulfate (SDS) micelle . The detergent head groups of SDS may be designed to physically mimic the surface of a biological membrane.…”
Section: Introductionmentioning
confidence: 99%